THE PREVALENCE OF PERIODONTAL TISSUE DISEASES IN YOUNG INDIVIDUALS ON THE BACKGROUND OF CROWDED TEETH - A.V. Mandych (Ukrainian Medical Stomatological Academy, 2018)
The abnormalities of maxillodental system take one of the leading places among diseases of the maxillofacial area. Thus, they are diagnosed more than in 50% cases among the younger population and in 30% cases among the adult population.   Most often, there are prerequisites for the incorrect position of individual teeth: anomalies are formed at the genetic level because of heredity of pathologies of size, amount, shape of teeth and size of the jaw bones of the facial skeleton. If the position of the teeth is incorrect, the periodontium retains the occlusal load of the functional injury. Therefore, the aim of our research was to study the prevalence of periodontal tissue diseases in young individuals on the background of crowded teeth. The material and research methods. The study was conducted on the base of Dental Center of Danylo Galytsky Lviv National Medical University during 2015−2017 years. 1146 people at the age from 18 to 44 years were examined. Every participant of research underwent general dental examination, as well as a special examination aimed at clarification of orthodontic treatment. The diagnosis of periodontal tissue diseases was made according to the classification of N. F. Danilevskyi and was determined using paraclinical indicators. The obtained results were worked out statistically using functions of MS Excel and Statistica 6. Results of the research and their discussion. The total number of the examined with orthodontic pathology was found on average in 77.24% of patients (885 people). At the same time, abnormalities of dental jaw system were not detected in about 261 (22.76%) of the examined. As a result of the conducted studies we found that among the examined without dental jaw abnormalities 38.89±.,32% of patients had intact periodontium, that was 1.6 times more for data in individuals with crowding − 23.73±2.00, p<0.01. At the same time, in patients of the main group the prevalence of periodontal tissue diseases was 1.2 times higher than in the examined of the comparative group (76.27±2.00% against 61.11±3.32%, respectively, p<0.01). It should be noted, that with the increase of the age of patients the prevalence of periodontal tissue diseases increased in both study groups, but in patients with crowded teeth this tendency was more pronounced. So, in the younger age group in patients with crowding the prevalence of periodontal diseases was 1.5 times higher in relation to the data of their peers from the comparison group (71.37±3.00% vs. 46.99±5.48%, p<0.01). In 27−35-year-old patients the prevalence of periodontal tissue diseases amounted to 72.38±4.03% of the examined of the main group and 65.62±5.94% of the examined of the comparison group, but the obtained data were not statistically significant, p>0.05. At the same time, in the patients of the main group aged 36−44 years the prevalence of periodontal tissue diseases was maximal and exceeded the value of their peers in the comparison group by 1.2 times (92.08±2.69% vs. 73.91±5.29%, respectively, p<0.01). The analysis of the obtained data allowed to assert that on average crowding of teeth on the upper jaw was found in 237 patients (52.55%) and on the lower jaw in 214 patients (47.45%). Thus, the maximum frequency of crowded teeth on the upper jaw was observed in the examined in the age range of 27−35 years, 60.16±4.41% of patients, with the minimum prevalence of this pathology in the youngest group (18−26 years), 49.34±4, 72%. The analysis of diagnostic structure of periodontal tissue diseases showed that inflammatory diseases of periodontal tissues (gingivitis, localized periodontitis) were found in patients with crowded teeth, on average 1.2 times more often than in patients without orthodontic pathology (42.42±1.88% vs. 36.33±3.54%, respectively, p<0.05). Conclusions. Thus, as a result of the conducted studies, higher prevalence of periodontal tissue diseases was proved in patients with crowding of teeth, which made progress in increasing the age of the examined than in patients without orthodontic pathology.